Investigating the phytochemical production and antioxidant activity in four plant species belonging to the asteraceae family - Le, Thi Van Anh; Tran, Ngoc Trung Anh; Dinh, Thi Hien Diu; Duong, Phuong Anh; Ha, Tran Bao Chau; Mai, Nga Thi Phuong (Vietnam Journal of Biotechnology, 2024)
Vietnam has a rich and profound traditional medicine system that is widely used today. Medicinal plants are used to treat colds, coughs, bone and joint diseases, digestion, respiratory diseases, etc. In this study, leaves of Artemisia vulgaris, Taraxacum officinale, Blumea balsamifera, and flowers of Xerochrysum bracteatum from the Asteraceae family were selected to determine the antioxidant capacity and relationship with the active ingredients in the plants. The methanolic extracts were screened for chemical compositions via the total phenolic content (TPC) assay, the total flavonoid content (TFC) assay, and DPPH radical scavenging activity. The highest radical scavenging activity was observed in the flowers of X. bracteatum (IC50 = 0.061 mg/mL), followed by the leaves of Taraxacum (IC50 = 0.313 mg/mL), A. vulgaris (IC50 = 1.367 mg/mL), and B. balsamifera (IC50 = 1.4502 mg/mL). The TPC of the studied plants ranged from 19.98 ± 1.355 to 195.78 ± 42.518 mgGAE/g extract, while the TFC ranged from 60.31 ± 1.725 to 339.14 ± 26.299 mgQE/g extract. The highest TPC and TFC were recorded in the methanol extract of X. bracteatum. The strongly negative correlation between the TPC and TFC and the IC50 values ​​(R2 = -0.78, R2 = -0.76) suggests that TFC and TPC could strongly contribute to the antioxidant activity of these plants. These results not only highlight the relevance of these plants in traditional medicine but also scientifically validate their use, particularly in the context of their antioxidant properties. The study underscores the close relationship between the traditional use of these plants and their scientifically observed effects, reinforcing the value of folk remedies.